Recent Clinical Evidence in Bisphosphonate-related Osteomyelitis of the Jaw: Focus on Risk, Prevention and Treatment - Yamazaki, Toru; Takahashi, Katsu; Bessho, Kazuhisa (Reviews on Recent Clinical Trials, 2014)
Bisphosphonates (BPs) are widely used for the treatment of a range of conditions involving bone, such as osteoporosis and bone metastases of cancer, and their efficacy has been confirmed. Nevertheless, a first case of bisphosphonate- related osteonecrosis of the jaw (BRONJ) as an adverse effect of BP treatment was reported in 2003, and several clinical studies since then have elaborated the risk, prevention and treatment of BRONJ or bisphosphonate-related osteomyelitis of the jaw (BROMJ). However, effective decision making on BP risk is hampered by a lack of accurate information for patients, physicians or dentists. Furthermore, the narrow definition of BRONJ used to date has precluded the wider development of clinical research on risk. In this review, we discuss current issues in BROMJ, with a focus on risk, prevention and treatment. In particular, we reconsider the definition of BRONJ from the standpoint of clinical evidence. Finally, we propose a new strategy for the treatment of BROMJ.
Keywords: relative risk